Compliance of nursing care practices with technical recommendations for normal birth - Natasha Faria Barros Guida; Adriana Lenho de Figueiredo Pereira; Gabrielle Parrilha Vieira Lima; Marcele Zveiter; Carla Luzia França Araújo; Maria Aparecida Vasconcelos Moura (Rev Rene)
Objective: to describe the compliance of obstetric nursing care practices with the technical recommendations for normal birth. Methods: cross-sectional study of records of normal birth care delivered by nurse-midwifes from two public maternity hospitals. The compliance assessment was based on the World Health Organization recommendations. The two-tailed Z-test was applied. Results: Appropriate compliance was found for all practices assessed at maternity hospital A. At maternity hospital B, the timely clamping of the umbilical cord obtained partial compliance (70.9%). Prescriptions were found for a null diet, 85.7% and 59.8%; oxytocin during labor, 38.7% and 48.4%; and peri-parturient tocodynamometry, 30.5% and 47.2%, at maternity hospitals A and B, respectively. Conclusion: the presence of the companion; use of the partogram; non-pharmacological care; intermittent auscultation of fetal heart beat; non-supinal maternal position during child birth; and postpartum application of intramuscular oxytocin obtain appropriate compliance, although inappropriate conducts were observed, such as prescriptions for a null diet, oxytocin and intrapartum tocodynamometry.